Deskripsi Kesulitan Belajar Peserta Didik pada Pembelajaran IPA Kelas VIII SMPN se-Kecamatan Bissappu (Studi pada Materi Pokok Sistem Pencernaan Pada Manusia) - Reski Wahyuni; Arie Arma Arsyad; Salma Samputri (Universitas Negeri Makassar, 2026)
This study aims to determine the description of learning difficulties of VIII grade students of SMPN in Bissappu District. This type of research was a descriptive survey. The population of this study were students of grade VIII of junior high schools in Bissappu District, Bantaeng Regency, namely SMPN 1 Bissappu, SMPN 2 Bissappu, and SMPN 3 Bissappu. The sampling technique used was random sampling technique so that a sample of 207 students was obtained. The research instrument used was a questionnaire of 34 statements. The results showed that the students' learning difficulties with an average score of 93.06 were in the moderate category. The three indicators causing the highest learning difficulties are psychological factors (27.21), school environment (21.79), and family environment (20.97). Meanwhile, biological factors and the community environment are in the low category with an average score of (11.33) and (11.04).